Gen-Z Melek Finansial Melalui Pengenalan Laporan Keuangan Pada SMK 1 Padang Panjang dan SMA Muhammadiyah Padang Panjang - Indrayeni, Indrayeni; Raflis, Ratnawati; Rahmaita, Rahmaita; Nini, Nini; Yan Fitri, Mellyna Eka; Riski, Tri Rachmat (LPPM Universitas Dharma Andalas, 2025)
Improving accounting knowledge at the high school/vocational school level is very necessary, considering that accounting is one of the competencies offered at these schools. In order to provide in-depth knowledge about finance, a team of lecturers from Dharma Andalas University held a community service activity at SMK 1 Padang Panjang and SMA Muhammadyah Padang Panjang. This activity was carried out by providing material related to knowledge about financial reports in accordance with current accounting standards. The number of students who participated in the PKM activity was SMK 1 Padang Panjang as many as 61 people and SMA Muhammadiyah Padang Panjang as many as 26 people. After this activity was carried out, students of SMK 1 Padang Panjang and SMA Muhammadyah Padang Panjang knew the types and forms of company financial reports in accordance with current standards.